Alterações na composição da comunidade de aves em uma área de Mata Atlântica no sudeste do Brasil submetida à restauração ecológica - Melo, Marcos Antônio (Universidade Federal de São Carlos, 2017)
The Atlantic Forest has experienced great loss of habitats and biodiversity as a consequence of human activities. Currently, most forest remnants are reduced and isolated in human-made landscapes. In this dramatic situation, ecological restoration has been a viable tool for rebuilding habitats to rescue part of their biodiversity, along with their complex ecological interactions and ecosystem services. Due to their biological characteristics, birds have been a good study model to evaluate the effectiveness of restored areas in providing suitable habitats for the fauna. Several studies have been conducted focusing this subject in North America and Europe, but there is little evidence of how restored areas affect bird communities in Latin America, mainly in Brazil. Here we characterized the avifauna in an ecological restoration area and tested how the age and structural complexity of the vegetation of these plantations influence the structuring of functional groups of birds compared to unrestored areas. For this, we collected data from avifauna for 12 months (from January to December 2015), by 39 fixed-point counts, sampled with a detection radius of 60 m. Sampled species were classified according to trophic and nesting groups, sensitivity levels and forest dependence. We recorded 208 species of birds, of which 172 were detected by point counts. Our results evidence that restored areas are capable of shifting the structure and composition of bird assemblages according to the age and vegetation structural complexity. Older restorations (6-7 years old) provided structurally more complex habitats than pastures and more recent restoration (4-5 years), thus reducing the abundance of forest-independent species, more common in early stages of succession, such as aerial insectivorous and granivores and insectivores of open habitats. This occurred due to the gradual substitution of the high percentage of grasses by the increase in the richness of arboreal morphospecies and canopy cover. Thus, our data corroborate with the theory of environmental heterogeneity; more complex environmental categories (RO and FR) provided more specific foraging and nesting sites, evidenced by the greater abundance of specialist groups, including insectivorous (trunk, canopy and foliage), nectarivores and small frugivores, as well as birds that use closed nests and rely on specific resources to build nests. In some cases, we found a trend of RO to resemble forest fragments of reference. Invariably, percentage of exotic grasses, distance of water resources, richness of arboreal species and canopy cover were important predictors for the structuring of guilds. Therefore, considering the current scenario of degradation of the Atlantic Forest, areas of ecological restoration can assist in the rescue of part of bird diversity, as well as in the restructuring of functional groups essential to the functioning of the ecosystem, even in restored areas less than 10 years old. Our results may be useful for future ecological restoration programs as a strategy to increase habitat for birds in highly fragmented areas.
Keywords: Avifauna; Dependência de florestas; Ecologia de restauração; Guildas tróficas; Sensibilidade ambiental; Variáveis ambientais; Restoration ecology; Foraging guilds; Enviromental sensibility; Forest dependence; Enviromental variables; CIENCIAS BIOLOGICAS::ZOOLOGIA::ZOOLOGIA APLICADA::CONSERVACAO DAS ESPECIES ANIMAIS